Bladder carcinogenesis in rats subjected to ureterosigmoidostomy and treated with L-lysine - Dornelas,Conceição Aparecida (2016)
ABSTRACT Objective: to evaluate the effect of L-lysine in the bladder and intestinal epithelia in rats submitted to vesicosigmoidostomy. Methods: we divided forty Wistar rats into four groups: group I - control group (Sham); group II - submitted to vesicosigmoidostomy and treated with L-lysine 150mg/kg; group III - submitted only to vesicosigmoidostomy; and group IV - received L-lysine 150mg/kg. After eight weeks the animals were sacrificed. Results: in the bladders of all operated animals we observed simple, papillary and nodular hyperplasia of transitional cells, transitional cell papillomas and squamous metaplasia. As for the occurrence of aberrant crypt foci in the colons of operated animals, we did not observe statistically significant differences in any of the distal, proximal and medium fragments, or in all fragments together (p=1.0000). Conclusion: Although statistically there was no promotion of carcinogenesis in the epithelia of rats treated with L-lysine in the observed time, it was clear the histogenesis of bladder carcinogenesis in its initial phase in all operated rats, this being probably associated with chronic infection and tiny bladder stones.